2017
DOI: 10.3389/fendo.2017.00238
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Ideas, Foundational Experiments (FIFE): Immunology and Diabetes 2016 FIFE Symposium

Abstract: The first Fresh Ideas, Foundational Experiments (FIFE): Immunology and Diabetes symposia workshop took place in 2016 and exemplified the active interest of a number of several investigators interested the global rise in the incidence of type 1 diabetes (T1D). This increase does not correlate with genetic drift and indicates that environmental exposures are playing an increasingly significant role. Despite major biomedical and technological advances in diagnosis and treatment, treatments are frequently insuffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Studies have reported that the expression of LAG-3 in naïve CD4+ T cells contributes to the restriction of mitochondrial biogenesis and cellular metabolism to keep T cells quiescent. Loss of LAG-3 in NOD mice leads to accelerated T1D progression, potentially by enhancing OXPHOS and glycolytic metabolism and promoting mitochondrial biogenesis of CD4+ T cells (102,108,109).…”
Section: Metabolic Interventions: a New Opportunity For T1d Treatmentmentioning
confidence: 99%
“…Studies have reported that the expression of LAG-3 in naïve CD4+ T cells contributes to the restriction of mitochondrial biogenesis and cellular metabolism to keep T cells quiescent. Loss of LAG-3 in NOD mice leads to accelerated T1D progression, potentially by enhancing OXPHOS and glycolytic metabolism and promoting mitochondrial biogenesis of CD4+ T cells (102,108,109).…”
Section: Metabolic Interventions: a New Opportunity For T1d Treatmentmentioning
confidence: 99%